The unfolding palette of COVID-19 multisystemic syndrome and its neurological manifestations - Barrantes, Francisco Jose (2021)
Although our current knowledge of the pathophysiology of COVID-19 is still fragmentary, the information so far accrued on the tropism and life cycle of its etiological agent SARS-CoV-2, together with the emerging clinical data, suffice to indicate that the severe acute pulmonary syndrome is the main, but not the only manifestation of COVID-19. Necropsy studies are increasingly revealing underlying endothelial vasculopathies in the form of micro-haemorrhages and micro-thrombi. Intertwined with defective antiviral responses, dysregulated coagulation mechanisms, abnormal hyper-inflammatory reactions and responses, COVID-19 is disclosing a wide pathophysiological palette. An additional property in categorising the disease is the combination of tissue (e.g. neuro- and vasculo-tropism) with organ tropism, whereby the virus preferentially attacks certain organs with highly developed capillary beds, such as the lungs gastrointestinal tract, kidney and brain. These multiple clinical presentations confirm that the acute respiratory syndrome as described initially is increasingly unfolding as a more complex nosological entity, a multiorgan syndrome of systemic breadth. The neurological manifestations of COVID-19, the focus of this review, reflect this manifold nature of the disease.